Comparative metabolomics reveals eggshell translucency formation using LC-MS Analysis - Ying Ma; Zhonghua Ning (Poultry Science)
Eggshell translucency is the common problem on eggshell that become more severe with age. They are important because it influence consumer preferences and the economic value of eggs. The reason for the eggshell translucency is currently believed to be the eggshell membrane (ESM). In this study, we screened translucency eggs and normal eggs and used metabolomics to study liver metabolism in different eggshell translucency and discuss important liver lipids and phosphatidyl metabolites. Liver samples were taken for Liquid Chromatograph Mass Spectrometer (LC-MS) during the formation of eggshell membranes in hens, that is, when eggs form eggshell membranes in the oviduct isthmus. The results showed that we identified two essential metabolic pathways through differential metabolite pathway analysis, which were glycine, serine, and threonine metabolism related to amino acids metabolism and the PPAR metabolic pathway related to lipid metabolism. Furthermore, this study helps us understand the process of translucency egg production in poultry. This laid the foundation for in-depth research on eggshell translucency. These results may and provide support for future breeding.